Activation of the Ataxia Telangiectasia Mutated/Autophagy pathway by a G-quadruplex ligand links senescence with apoptosis. (4th July 2019) - Beauvarlet, Jennifer; Mergny, Jean-Louis; Djavaheri-Mergny, Mojgan
ABSTRACT: G-quadruplex (G4) ligands have shown anti-tumor activity by stabilizing G4 structures. We recently reported that the G4 ligand20A promotes senescence in cancer cells through Ataxia Telangiectasia Mutated (ATM) and autophagy activation. Inhibition of both pathways directs cells to apoptosis, positioning ATM/autophagy axis as a linchpin between senescence and apoptosis.